The influence of Fear of Missing Out (FOMO), Social Validation, and Influencer Marketing on Generation Z’s Impulsive Buying Purchasing Behavior in Pop Mart - Ivan Ardianto; Kardina Yudha Parwati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Fear of Missing Out (FOMO), social validation, and influencer marketing on Generation Z’s impulsive buying behaviour at Pop Mart Indonesia. The research employs a quantitative approach with an explanatory research design and a survey method, involving 143 respondents who are Pop Mart customers aged between 17 and 28 years. Data were collected through an online questionnaire and subsequently analyzed using SPSS version 27 to examine the relationships among the variables. The findings indicate that FOMO, social validation, and influencer marketing collectively have a significant influence on impulsive buying behaviour. Among the three factors, FOMO demonstrates the strongest influence, while social validation contributes the weakest yet still meaningful effect. These results suggest that Gen Z’s urge to stay socially connected, combined with digital peer validation and influencer-driven content, significantly drives unplanned purchases. The outcomes of this study are expected to serve as a basis for ongoing evaluation in formulating effective marketing strategies for Pop Mart and similar industries in Indonesia, enabling a deeper understanding of Generation Z consumer dynamics in the digital era. Furthermore, this research aims to contribute both theoretically and practically by enriching the marketing literature regarding the psychological and social factors that drive impulsive behaviour among young consumers, while offering actionable insights for brands targeting digitally native audiences.